Global media versus peace journalism / Faridah Ibrahim - Ibrahim, Faridah (Centre for Media and Information Warfare Studies, 2008)
The mass media and their contents are integral to shaping the course of events in time of peace and war. With the proliferation of technology which brings in more rapid and intense coverage of events around the world, the connection between events, places, leaders, and people become increasingly clear. Mass media can be considered as one of the most powerful expressions of the "spirit" of our age. Mass media in the globalised world are undergoing a massive change and undeniably, technology is the driving force behind it.